Mobile banking or m-banking is becoming a prominent feature in banking operations in Nigeria with more and more banks adopting this technology in order to provide the growing population of their customers with fast, accessible, reliable and quality services. The technology of mobile banking has emerged as a possible powerful provider of bundle of banking services. The mobile banking system involves the use of a mobile device (e.g. phone) to pay for goods or services either at the point of sale or conduct of banking transactions anywhere and anytime. The study evaluated the attitude of bank customers towards the adoption of M-banking services and challenges of mobile phone in conducting banking transactions in Nigeria with analytical focus on Enugu State. The survey research approach was adopted and data were collected from 200 respondents that include bank staff and customers of selected banks in Enugu metropolis. The analysis of data was conducted using descriptive statistical technique. The study revealed that the level of adoption of mobile banking in Enugu State is still low among the middle aged respondents compared to the aged. A massive awareness program to publicize the purpose and benefits derivable from the use of mobile banking should be encouraged. This, it is hoped, will boost the level of adoption of mobile banking services because of the convenience and accessibility offered by this banking platform. (2016)
Mobile banking or m-banking is becoming a prominent feature in banking operations in Nigeria with more and more banks adopting this technology in order to provide the growing population of their customers with fast, accessible, reliable and quality services. The technology of mobile banking has emerged as a possible powerful provider of bundle of banking services. The mobile banking system involves the use of a mobile device (e.g. phone) to pay for goods or services either at the point of sale or conduct of banking transactions anywhere and anytime. The study evaluated the attitude of bank customers towards the adoption of M-banking services and challenges of mobile phone in conducting banking transactions in Nigeria with analytical focus on Enugu State. The survey research approach was adopted and data were collected from 200 respondents that include bank staff and customers of selected banks in Enugu metropolis. The analysis of data was conducted using descriptive statistical technique. The study revealed that the level of adoption of mobile banking in Enugu State is still low among the middle aged respondents compared to the aged. A massive awareness program to publicize the purpose and benefits derivable from the use of mobile banking should be encouraged. This, it is hoped, will boost the level of adoption of mobile banking services because of the convenience and accessibility offered by this banking platform.